2008
DOI: 10.2166/wst.2008.232
|View full text |Cite
|
Sign up to set email alerts
|

Savings with upgraded performance through improved activated sludge denitrification in the combined activated sludge–biofilter system of the Southpest Wastewater Treatment Plant

Abstract: The purpose of the experiments was to increase the rate of activated sludge denitrification in the combined biological treatment system of the Southpest Wastewater Treatment Plant in order to gain savings in cost and energy and improve process efficiency. Initial profile measurements revealed excess denitrification capacity of the preclarified wastewater. As a consequence, flow of nitrification filter effluent recirculated to the anoxic activated sludge basins was increased from 23,000 m3 d(-1) to 42,288 m3 d(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The denitrification process in the AeMBR or CAS is highly dependent on the recycle flow from the oxic (nitrification) to the anoxic tank and sometimes requires the supply of external carbon. External carbon dosage is costly and can lead to elevated BOD concentrations in the effluent when overdosed . One of the main advantages of the AGS process is that the biological nitrogen removal processes are not separated in different oxic and anoxic tanks.…”
Section: Resultsmentioning
confidence: 99%
“…The denitrification process in the AeMBR or CAS is highly dependent on the recycle flow from the oxic (nitrification) to the anoxic tank and sometimes requires the supply of external carbon. External carbon dosage is costly and can lead to elevated BOD concentrations in the effluent when overdosed . One of the main advantages of the AGS process is that the biological nitrogen removal processes are not separated in different oxic and anoxic tanks.…”
Section: Resultsmentioning
confidence: 99%
“…supported by full-scale experiments aiming increased denitrification efficiency at the Southpest WWTP (Jobbágy et al [11]). …”
Section: Resultsmentioning
confidence: 99%
“…Simulation studies with this model revealed that efficient backseeding may considerably improve performance by enhancing nitrification ability of the activated sludge unit, thereby facilitating considerable savings in both methanol and aeration costs. Full-scale results verified the applicability of the model, but long-term, efficient nitrification could not be achieved in the full-scale activated sludge unit although the enhanced activated sludge denitrification decreased the oxygen demand of carbon removal (Jobbágy et al [11]). No direct investigation of possibly facilitating efficient backseeding through increased activated sludge aeration had been carried out.…”
Section: Configuration Of the Treatment Plant And Preliminariesmentioning
confidence: 91%
See 1 more Smart Citation